THE CORRELATION BETWEEN BEHAVIOR AND SOCIO-ECONOMIC OF PARENTS AND OHI-S IN CHILDREN - Rizky Tania Shafira Afifa Zulkarnain; R. Harry Dharmawan Setyawardhana; Ika Kusuma Wardani (FKG Unlam, 2023)
Background: Based on Basic Health Research in 2018, children aged 5-9 years in South Kalimantan experienced tooth decay, cavities, or pain of 56.17%. Parents have an important role in forming the behavior of school-age children. Children will imitate the behavior of their parents. Purpose: Analyzing the correlation between parents' behavior and socioeconomic status of parents and OHI-S in children. Method: This study used an analytical research method with a cross-sectional approach. The number of samples in this study was 43 samples. The sample was determined by purposive sampling. The data collection techniques were conducted directly on parents and students at the Elementary School of Pemurus Dalam 1 Banjarmasin who met the inclusion criteria. The research instrument used was a questionnaire to measure the behavior and socioeconomic of parents. OHI-S was assessed based on the OHI-S index. Result: The data were analyzed using the Spearman test. The value significant was ρ=0.034 (ρ<0.05) for the behavior correlation of parents and OHI-S in children and the significant value was ρ=0.383 (ρ>0.05) for the socio-economic correlation of parents and OHI-S in children. Conclusion: There is a significant relationship between the behavior of parents on OHI-S in children and there is no significant relationship between the socioeconomic status of parents on OHI-S in children.Keywords: behavioral, children, OHI-S, socioeconomic